Super-natural fears. (September 2021) - Coelho, Carlos M.; Zsido, Andras N.; Suttiwan, Panrapee; Clasen, Mathias
Highlights: Supernatural fears and anxieties are widespread. Supernatural fears and anxieties are understudied. Many supernatural fears are variations on biologically prepared fears. The study of supernatural fears has significant clinical implications. Abstract: Supernatural fears, although common, are not as well-understood as natural fears and phobias (e.g., social, blood, and animal phobias) which are prepared by evolution, such that they are easily acquired through direct experience and relatively immune to cognitive mediation. In contrast, supernatural fears do not involve direct experience but seem to be related to sensory or cognitive biases in the interpretation of stimuli as well as culturally driven cognitions and beliefs. In this multidisciplinary synthesis and collaborative review, we claim that supernatural beliefs are "super natural." That is, they occur spontaneously and are easy to acquire, possibly because such beliefs rest on intuitive concepts such as mind-body dualism and animism, and may inspire fear in believers as well as non-believers. As suggested by psychological and neuroscientific evidence, they tap into an evolutionarily prepared fear of potential impending dangers or unknown objects and have their roots in "prepared fears" as well as "cognitively prepared beliefs, " making fear of supernatural agents a fruitful research avenue for social, anthropological, and psychological inquires.